2017
DOI: 10.3389/fmicb.2016.02129
|View full text |Cite
|
Sign up to set email alerts
|

TRIM5α Promotes Ubiquitination of Rta from Epstein–Barr Virus to Attenuate Lytic Progression

Abstract: Replication and transcription activator (Rta), a key protein expressed by Epstein–Barr virus (EBV) during the immediate-early stage of the lytic cycle, is responsible for the activation of viral lytic genes. In this study, GST-pulldown and coimmunoprecipitation assays showed that Rta interacts in vitro and in vivo with TRIM5α, a host factor known to be involved in the restriction of retroviral infections. Confocal microscopy results revealed that Rta colocalizes with TRIM5α in the nucleus during lytic progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Overexpression of TRIM5a reduces the transactivating capabilities of Rta, whereas reducing TRIM5a expression enhances EBV lytic protein levels and DNA replication. 175 …”
Section: Ebv and The Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of TRIM5a reduces the transactivating capabilities of Rta, whereas reducing TRIM5a expression enhances EBV lytic protein levels and DNA replication. 175 …”
Section: Ebv and The Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
“…Overexpression of TRIM5a reduces the transactivating capabilities of Rta, whereas reducing TRIM5a expression enhances EBV lytic protein levels and DNA replication. 175 Besides utilizing host DUBs, EBV can also encode the viral deubiquitinating enzyme (v-DUB), BPLF1, which is an immune evasion gene product that can suppress antiviral immune responses during primary infection. BPLF1 is expressed during the late phase of lytic EBV infection and is incorporated into viral particles.…”
Section: Ebv and The Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
“…Herpesviruses are also susceptible to TRIM5α, with the replication and transcription activator (Rta) from Epstein-Barr virus (EBV) as an identified target [74]. MS screening of host factors that interact with Rta identified TRIM5α and further characterization revealed that both factors interact in the nucleus [74]. Rta functions during the immediate-early stage of EBV infection and facilitates the transcription of EBV lytic genes that initiate progeny virion formation and release [74].…”
Section: Proteasome-dependent Antiviral Mechanismsmentioning
confidence: 99%
“…MS screening of host factors that interact with Rta identified TRIM5α and further characterization revealed that both factors interact in the nucleus [74]. Rta functions during the immediate-early stage of EBV infection and facilitates the transcription of EBV lytic genes that initiate progeny virion formation and release [74]. This process is subdued by TRIM5α through Rta targeting for ubiquitination and proteasomal degradation, suggesting nuclear TRIM5α maintains EBV latency in infected cells [74].…”
Section: Proteasome-dependent Antiviral Mechanismsmentioning
confidence: 99%
“…Epstein–Barr virus (EBV) replication and transcription activator (Rta) protein activates EBV lytic genes for proliferation [ 238 ]. TRIM5α promotes the ubiquitination of Rta upon interaction, thereby blocking the EBV lytic cycle [ 238 ]. The involvement of TRIM5α in a non-retroviral innate immune response implies TRIMs possess diverse, situation-specific functions that have yet to be characterized.…”
Section: Trim-mediated Virus Inhibitionmentioning
confidence: 99%